Longitudinal Analysis of Quality of Life, Clinical, Radiographic, Echocardiographic, and Laboratory Variables in Dogs with Preclinical Myxomatous Mitral Valve Disease Receiving Pimobendan or Placebo: The EPIC Study. (6th December 2017) - Boswood, A.; Gordon, S.G.; Häggström, J.; Wess, G.; Stepien, R.L.; Oyama, M.A.; Keene, B.W.; Bonagura, J.; MacDonald, K.A.; Patteson, M.; Smith, S.; Fox, P.R.; et al.
Abstract : Background: Changes in clinical variables associated with the administration of pimobendan to dogs with preclinical myxomatous mitral valve disease (MMVD) and cardiomegaly have not been described. Objectives: To investigate the effect of pimobendan on clinical variables and the relationship between a change in heart size and the time to congestive heart failure (CHF) or cardiac‐related death (CRD) in dogs with MMVD and cardiomegaly. To determine whether pimobendan‐treated dogs differ from dogs receiving placebo at onset of CHF. Animals: Three hundred and fifty‐four dogs with MMVD and cardiomegaly. Materials and Methods: Prospective, blinded study with dogs randomized (ratio 1:1) to pimobendan (0.4–0.6 mg/kg/d) or placebo. Clinical, laboratory, and heart‐size variables in both groups were measured and compared at different time points (day 35 and onset of CHF) and over the study duration. Relationships between short‐term changes in echocardiographic variables and time to CHF or CRD were explored. Results: At day 35, heart size had reduced in the pimobendan group: median change in (Δ) LVIDDN −0.06 (IQR: −0.15 to +0.02), P < 0.0001, and LA:Ao −0.08 (IQR: −0.23 to +0.03), P < 0.0001. Reduction in heart size was associated with increased time to CHF or CRD. Hazard ratio for a 0.1 increase in ΔLVIDDN was 1.26, P = 0.0003. Hazard ratio for a 0.1 increase in ΔLA:Ao was 1.14, P = 0.0002. At onset of CHF, groups were similar. Conclusions and Clinical Importance: Pimobendan treatment reduces heart size. Reduced heart size is associated with improved outcome. At the onset of CHF, dogs treated with pimobendan were indistinguishable from those receiving placebo.